Holistic Life‐Cycle Analysis of Bridge Solutions. Issue 2 (1st September 2021) - Zinke, Tim; Hechler, Oliver; Rademacher, Dennis
Abstract: Steel in bridge constructions is often associated with very large span bridges due to its favorable relationship between strength and weight. But even for bridges with small and medium spans of up to 60 m, steel combined with concrete as a composite bridge can lead to economically justifiable constructions, especially when the performance during the complete life‐cycle is integrated. In this paper, two life‐cycle oriented calculation methods (life‐cycle costs and external costs) are introduced and applied. As a result, comparisons between two abutment solutions (conventional reinforced concrete abutment and a permanent steel sheet pile abutment) and two superstructure variants (steel composite construction and in‐situ prestressed concrete superstructure) are presented. It is shown that accelerated construction processes, durable materials, and a smart bridge‐design considering actual technological developments lead to economically advantageous solution for traffic infrastructures.